Circulating long non-coding RNAs detection after heart transplantation and its accuracy in the diagnosis of acute cardiac rejection - Lorena Pérez-Carrillo; Isaac Giménez-Escamilla; Irene González-Torrent; Marta Delgado-Arija; Ignacio Sánchez-Lázaro; María García-Manzanares; Luis Martínez-Dolz; Manuel Portolés; Estefanía Tarazón; Esther Roselló-Lletí (BMC, 2024)
Abstract Long non-coding RNAs (lncRNAs) are closely implicated in biological processes and diseases with high inflammatory components. These molecules exhibit significant temporal and tissue specificity. However, the expression and function of lncRNAs have not been studied in patients after heart transplantation. Thus, we aimed to identify circulating lncRNAs in these patients and evaluate their diagnostic capacity as potential biomarkers for the non-invasive detection of acute cellular rejection (ACR). For them, we performed a transcriptomic study based on ncRNA-seq technology to detect lncRNAs in serum samples, matched to routine endomyocardial biopsies, from patients without rejection episode (0R, n = 12) and with mild (1R, n = 16) or moderate-severe (≥ 2R, n = 12) ACR. We identified 11,062 circulating lncRNAs in the serum of patients after heart transplantation. Moreover, 6 lncRNAs showed statistically significant expression when the different ACR grades were compared. Among them, AC008105.3, AC006525.1, AC011455.8, AL359220.1, and AC025279.1 had relevant diagnostic capacity for detection of ≥ 2R (AUC of 0.850 to 1.000) and 1R (AUC of 0.750 to 0.854) grades, along with high specificity and positive predictive values (≥ 83%). In addition, AL359220.1 and AC025279.1 were independent predictors for the presence of moderate-severe ACR (odds ratio = 31.132, p < 0.01 and C statistic = 0.939, p < 0.0001; odds ratio = 18.693, p < 0.05 and C statistic = 0.902, p < 0.001; respectively). In conclusion, we describe, for the first time, circulating lncRNAs after heart transplantation as potential candidates for non-invasive detection of ACR. AL359220.1 and AC025279.1 showed excellent diagnostic capability correlating with the severity episode and were strong independent predictors of rejection.